Power Domination and Resistance in Nawal El Saadawi's Mawtu Ma'ali Al-Waziri Sabiqan: Antonio Gramsci's Hegemony - Hidayat, Ridho; Rohanda, Rohanda; S, Dendi Yuda (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research explores the dynamics of hegemony and resistance in Nawal El Saadawi’s novel Mawtu Ma‘ali al-Waziri Sabiqan through the lens of Antonio Gramsci’s theory of cultural hegemony. The research takes Gramsci’s concepts of ideological domination and counter-hegemonic struggle as its formal object, while the novel serves as the material object. Using a qualitative descriptive approach and a critical reading method grounded in ideological literary theory, this research positions itself within contemporary Arabic literary research that intersects with cultural-political analysis. The findings indicate that power in the novel operates not only through coercive mechanisms but also through ideological consent embedded within social institutions and dominant narratives that regulate behavior, identity, and voice. Resistance emerges as both symbolic and material acts of defiance that challenge the prevailing ideological structures. This research highlights literature as a site of negotiation between power and ideology, offering valuable insight for literary and cultural studies in understanding how texts mediate sociopolitical relations and contestations. ملخص تستكشف هذه الدراسة ديناميكيات الهيمنة والمقاومة في رواية نوال السعداوي